(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: The alloreactivity of natural killer cell and certain subsets of T lymphocyte are regulated by the interaction between killer immunoglobulin-like receptors (KIRs) of donor cells and human leukocyte antigen (HLA)-class I molecules on target cells. The interaction has been shown to influence the outcome of allogeneic haematopoietic stem cell transplantation (HSCT). Homozygous C1 or C2 and heterozygous C1/C2 were divided by HLA-Cw typing and they influenced the outcome of HSCT. OBJECTIVE: The purpose of the study was to analyse the impact of interaction between recipient HLA-Cw and donor KIR on outcome. METHODS: The genotypes of recipient HLA-Cw ligands and donor KIRs were correlated with the clinical outcomes of 52 patients who received HLA-matched, sibling donor HSCT for myeloid malignancies. RESULTS: The incidence of chronic graft versus host disease (GVHD) was significantly lower in C1 or C2 homozygotes than in C1/C2 heterozygotes (p = 0.000). Higher overall survival (OS) and disease-free survival (DFS) rates were observed in C1 or C2 homozygotes than in C1/C2 heterozygotes (OS, 81% ± 8% vs 54% ± 10%, p = 0.034; DFS, 81% ± 8% vs 54% ± 10%, p = 0.024). A lower incidence of chronic GVHD and higher OS and DFS were observed in the HLA-KIR mismatched group (chronic GVHD, p = 0.007; OS, 84% ± 7% vs 47% ± 13%, p = 0.003; DFS, 84% ± 7% vs 47% ± 13%, p = 0.002). CONCLUSION: The interaction between recipient HLA ligand and donor KIR had a significant impact on the outcome of patients receiving matched sibling HSCT. C1/C2 heterozygotes or HLA-KIR matched patients may benefit from additional intensified therapy with better outcome.